Numerical study on turbulent forced convective heat transfer using nanofluids TiO2 in an automotive cooling system - Hussein A.M.; Dawood H.K.; Bakara R.A.; Kadirgamaa K. (Elsevier Ltd, 2023)
Automobile cooling systems; Automobile radiators; Computational fluid dynamics; Friction; Heat convection; Nanoparticles; Nusselt number; Radiators; Reynolds number; Thermodynamic properties; Titanium dioxide; Tribology; Car radiators; Forced convective heat transfer; Friction factors; Heat transfer efficiency; Nanofluids; TiO2 nano-particles; Turbulent convective heat transfers; Volume concentration; Nanofluidics